National personnel policy in the state-party apparatus of the Kazakh SSR in 1945–1991 (Journal of history-rus, 2023)
Abstract. The top party leadership emphasized the importance of proper representation of all nations in state and party bodies, so that the composition of leadership cadres would sufficiently reflect the national structure of the population, which had specific needs in the field of everyday life, culture, and language. The formation of national cadres was under the close control of the Party leadership and was an important element of the national policy of the USSR. This is evidenced by numerous meetings of the CPSU Central Committee, conferences, plenums, congresses, etc.The purpose of this article is to analyze the national personnel policy in the state-party apparatus of the Kazakh SSR. Based on archival documents and statistical materials, the authors traced the trends in the selection and placement of personnel. The main objective of the article is to analyze the data on the dynamics of national cadres in the period from 1945 to 1991.The article uses published and unpublished archival materials of the Archive of the President of the Republic of Kazakhstan, the State Archive of the Russian Federation, as well as data of official statistics.The article was made within the framework of realization of scientific project «Zhas galym» IRN AP4972994 «Soviet national policy and problems of interethnic relations in Kazakhstan in 1945-1991».